Pelatihan Pemanfaatan Canva untuk meningkatkan Kreatifitas dan Literasi Digital Siswa SD Wonoasri 02 Madiun - Hani Atun Mumtahana; Noordin Asnawi; Mei Lenawati; Umar Faruq; Azza An Nushi; Dewy Reygyna (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The development of digital technology requires schools to be able to implement the use of digital technology in the learning process. The use of digital technology in the learning process can improve the digital literacy of teachers, students, and the community in the school environment. In addition, the use of digital technology can improve students' competence in using digital technology in the learning process. One digital technology that can be used by students in the learning process is Canva as a graphic design application. However, the use of graphic design applications as a learning medium at SDN Wonoasri 02, Madiun Regency is still not optimal because students do not have the knowledge and skills in using the Canva application. This community service activity aims to improve digital literacy, creativity, and students' abilities in using Canva as a learning medium. The target of the activity is 21 students in grades IV and V. The methods used include observation, pretest, material delivery, demonstration, direct practice, mentoring, posttest, and product assessment. Evaluation is carried out using pretest and posttest instruments, observation sheets, and product assessment based on theme suitability, creativity, neatness of layout, and the ability to convey information visually. The results of the activity showed that the average pretest score increased from 53.8% to 89.8% in the posttest, representing a 36.0% increase. The product assessment obtained an average score of 89, categorized as good, indicating that students were able to produce learning products using a simple digital learning medium, Canva. This activity has proven effective in improving students' digital literacy competencies and creativity and has the potential to support the implementation of technology-based learning in elementary schools.